AFFIXES FORMING PASSIVE VERBS IN BUGIS LANGUAGE - Makkawaru, Makkawaru (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. The problem of this research is the affixation of Bugis language, which is limited to three subproblems namely; affix form, function, and meaning in Bugis language. Affixation is described as descriptly and qualitatively. The data source is in the form of utterances from native speakers of the Bugis language. Data collection techniques are direct interview techniques, namely fishing techniques, the designation of activities, designation of images, and documentary studies. The technical analysis used in research is to transcribe data, then transcribe it into written form, then classified according to the problem. Based on the analysis of existing data, the results of the study show that the affixes in Bugis language have form, function, and meaning. The form of affixes in Bugis language are: Prefixes {ta-}, {ri-}, {na-}, {ripa-}, double affixes {na -, - ngi}, {ri -, - eng}, {ri + aG -, -ang}. Function: changing the word class and not changing the word class. The meaning of affixes forming passive verbs in Bugis language is Prefix {ta-}: Stating a sudden or unintentional event, and stating an action that is subject to work referred to in the root word, {ri-}: Stating the action being taken work called the root word, {na-}: Stating the action that is subject to work which is called the root word, {ripa-}: States the causative meaning. Meaning of double affixes {na-,-ngi}: Stating is made as stated in the basic form, {ri-, -eng}: Stating the action mentioned in the basic form, {ri- + aG-, -ang}: Stating the action mentioned in the basic form.